Effect of transfer in the acquisition of English preposition by L1 Turkmen speakers - Ejegul Shaviyeva (2015)
This study investigated the effect of transfer in the acquisition of English prepositions by first language (L1) Turkmen and second language (L2) English learners. The study tested the Full transfer/Full access hypothesis (FTFA) proposed by Schwartz and Sprouse (1996). The hypothesis argues that L2 learners initially transfer all the parameter-settings from their mother tongue and thereafter, reset the L1 parameter to the L2 parameter. In addition, the data collected tested two more hypotheses, i.e. the Missing Surface Inflection Hypothesis (MSIH) proposed by Prevost and White (2000) and Failed Functional Features Hypothesis (FFFH) by Hawkins and Chan (1997). The Missing Surface Inflection Hypothesis (MSIH) (Prevost & White, 2000) claims that underlying correct morphosyntax of L2 can be acquired by L2 learners and inconsistent errors of L2 learners are not the result of underlying syntactic deficit; instead, they are regarded as missing inflections which cause performance errors. The Failed Functional Features Hypothesis (FFFH) by Hawkins and Chan (1997) proposes that parameterized L2 functional features may not be acquired by L2 learners past a critical period. This study was inspired by two languages with dissimilar parameter features i.e.,English, an analytic language, and Turkmen, an agglutinative language. A difference between the two languages is English has prepositions and Turkmen has postpositions. Participants of this study were 78 L1 Turkmen speakers from a language center in Dashoguz, Turkmenistan. The Oxford Placement Test (OPT) was administered to place them in three different levels of proficiency (elementary,intermediate, advanced). Based on a comparative analysis of the preposition and post-position systems in the two languages, a Grammaticality Judgment Task (GJT) was formulated. This was administered to test participants’ knowledge of English prepositions. The GJT consisted of 18 grammatical items (6 with locational prepositions, 6 with directional prepositions and 6 with ambiguous prepositions) and 18 ungrammatical items (6 with locational prepositions, 6 with directional prepositions and 6 with ambiguous prepositions). The data collected with the GJT revealed (a) to what extent L1 Turkmen speakers of L2 English are able to acquire the surface structure of locational, directional and ambiguous prepositions in English, (b) types of errors in the use of prepositions that are more likely to be committed by Turkmen ESL learners, (c) the role of L2 transfer in the acquisition of English prepositions by L1 Turkmen speakers. In addition, a Gap Filling Task (GFT) was used to investigate the effect of L1 on the L2. The findings of the study suggested that the majority of L1 Turkmen L2 English learners showed remarkable performance in recognizing and judging the surface structure of the grammatical items with English directional and ambiguous prepositions from the ungrammatical items. On the other hand, participants were less determinate in judging grammatical locational prepositions from ungrammatical ones. The results of the GJT revealed that L1 Turkmen L2 English learners were able to acquire the surface structure of English prepositions; in addition, the results of the GFT suggest that the L1 does have an effect on L2 acquisition. In addition, the results suggest that errors committed by the participants are not consistent, which is compatible with the findings of the studies that support MSIH and FTFA. The results of this study will contribute to SLA literature on L1 transfer among ESL learners, and the developing field of education in Turkmenistan.